Physiological and phytosanitary potential of rocket seeds - Jucilayne Fernandes Vieira (Ciência Rural, 2015)
The objective of this study was to evaluate the physiological and sanitary quality of seeds of rocket; the research was done at the Laboratory of Seed Analysis and greenhouse of the Department of Plant Science, Federal University of Pelotas (UFPel). Four lots of the cultivar “Antonella’’ were tested for following features: initial and final moisture content, germination rate, first count of germination, accelerated aging with saline solution, dry matter contents, seedling shoot and root length, emergence speed index, emergence of seedlings in substrate, electrical conductivity and sanitary condition. A completely randomized design with four replications was used for all tests done and means were compared by Tukey test (P≤0.05). For all tests performed it was concluded that despite changes in the ranking of the best lots, there was agreement regarding the indication of the inferiority of the lot 3 in all tests and it was also observed that the incidence of fungi associated with seeds of rocket interfere with the physiological quality of the lots.